Sources of revenues formation of the budget subnational level and their classification - M. M. Yakhjyaev (Путеводитель предпринимателя)
The main objectives of the interbudgetary process in the Russian Federation are need ofincrease oftax capacity of regions of the Russian Federation, making essentialpart ofthe income ofthe budget of subnational level; increase ofprogressiveness of financial alignment of various regional budgets taking into account high asymmetry in development; need of providing a financial autonomy of municipalities within development ofthe decentralized form ofthe interbudgetary relations. All this complex of tasks is to some extent connected with research of questions of efficiency offormation and management of the budget income at subnational level.